Hubungan Antara Pendapatan Keluarga Dengan Penggunaan Metode Kontrasepsi Pada Pasangan Usia Subur di Desa Lengkong Kecamatan Garawangi Kabupaten Kuningan - Komsari Komsari; Asep Sufyan Ramadhy; Titing Hartiningsih (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2012)
Introuction: Many factors affecting contraceptive method usage behavior by fertile couple. One of them is family income. Currently the use of long-term contraceptives method is still not enough to attract by society compared with the short-term contraceptive methods, such as injections and pills. In many fertile couple’s perception, using injection and pill method is cheaper than Intra Uterine Devices or implant. Method: This research used cross-sectional design. The population is all the fertile couple in Lengkong District, Garawangi and the sample size is 259 fertile couples, is taken by simple random sampling technique. Data were collected using a questionnaire. Data were analyzed using Chi-Square test with significance level 0,05. Result: The results show that there is no significant association (p=0,641) between family income and the contraceptive usage behavior based on type. There is very significant association (p=0,000) between family income and the contraceptive usage behavior based on mechanism (mechanic vs hormonal – OR=4,830) and effect period (longterm vs short-term – OR=4,978). Discussion: The midwife has to promote intensively the family planning, especially related to the long-term contraceptive method usage, involve multistakeholders approach